Computational Fatigue Damage Prediction of the Lorry Frames under Random Excitation - Milan Vasko; Milan Saga; Bohus Leitner (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with FEM application in the TATRA 815 lorry frame construction fatigue life estimation. Construction of critical nodes from the fatigue damage point of view was found and analyzed. Analysis of the particular traffic state influence on the fatigue damage cumulation will be presented too.